Do hiring subsidies reduce unemployment among the elderly? Evidence from two natural experiments - Andreas Ammermüller; Thomas Zwick; Bernhard Boockmann; Michael Maier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
We estimate the effects of hiring subsidies for older workers on transitions from unemployment to employment in Germany. Using a natural experiment, our first set of estimates is based on a legal change extending the group of eligible unemployed persons. A subsequent legal change in the opposite direction is used to validate these results. Our data cover the population of unemployed jobseekers in Germany and was specifically made available for our purposes from administrative data. Consistent support for an employment effect of hiring subsidies can only be found for women in East Germany. Concerning other population groups, firms hiring behavior is hardly influenced by the program and hiring subsidies mainly lead to deadweight effects.
Keywords: C31; H24; J64; 330; Hiring subsidies; older workers; evaluation; natural experiments